The Implementation of the South African Language Policy by Local Government. A Case Study. - Mhlongo, Nobuhle (Linguistics, 2022)
In 1994, the South African democratic government declared 11 languages as official. Section (6) of the Constitution stipulates that all 11 official languages should enjoy equal status. Amongst other things, language policies, language institutions, and legislations were established to assist in implementing Section (6) of the Constitution. Provincial governments have been given the task to adopt a language policy that will ensure that the designated official languages are used, promoted, and developed equally. Mpumalanga has four designated official (provincial) languages: Afrikaans, English, isiNdebele, and SiSwati. This study aims to investigate the implementation of the South African language policy by a local municipality in Mpumalanga. The data presented in this thesis were gathered using semi-structured interviews with executive staff members as well as through questionnaires and office observations at the municipality. In addition, this thesis analysed physical municipal signage, Facebook posts by the municipality and members of the public, the official website of the municipality, and annual municipal reports. The findings indicate that there exist a variety of multilingual practices on the ground. However, these multilingual practices are mostly habitual and everyday; they are not due to the active implementation of a municipal language policy. Moreover, the findings of the study indicate that English is the preferred language at the municipality: English dominates in meetings, in written communication, on signage, official Facebook posts, and the website. The data also indicate that SiSwati has a strong presence at the municipality, but it is marginalised in other areas such as written and online communication. In addition, the data suggest that there is inequality in how the other provincial languages are used: there is only minimal presence of isiNdebele and Afrikaans. Moreover, Xitsonga, which is not a designated provincial language, has a strong presence in the municipality but no official status. This thesis argues that there is partial implementation of the language policy at the municipality. The challenges affecting the implementation includes the ideology around the use of English and the negative attitudes towards SiSwati that are present in the community. Lack of implementation is also a result of limited resources in the municipality. This thesis uses the data to formulate recommendations for the Mpumalanga provincial government. These recommendations can assist with the implementation of the language policy in government communication and the equal use of all the languages present in the municipality